Hidden champions, missed opportunities - European Investment Bank (European Investment Bank, 2024)
The report zooms in on the mid-cap category of firms, an essential part of the economy, but not well researched, partly due to a lack of a clear definition of these type of enterprises in statistical databases. To fill a gap in data availability and insights on this type of companies, this report provides insights on their performance, investment activities, financing needs, and the challenges that these companies face linked to the green, digital and economic security transitions. The research work is conducted using the EIB Group Survey on Investment and Investment Finance (EIBIS), the bank’s unique information source providing details on investment and financing decisions of 12 000 European small businesses (SMEs), mid-caps and very large (XL) firms on an annual basis.